First trimester glycated hemoglobin in the prediction of gestational diabetes mellitus - Ahmad T.A Fattah; Adel A Elboghdady; Mohammad E Abo-Ghabsha; Mahmoud A.G Ahmad (Wolters Kluwer Medknow Publications, 2020)
Background Gestational diabetes mellitus (GDM) is a serious disease, which may cause complications such as preeclampsia, increased cesarean rates, and macrosomia in mothers and neonates. Objective The aim of the study was to examine whether women who have a first trimester prediabetes − glycated hemoglobin (HbA1C) range of 5.7-6.4% are more likely to have an abnormal second trimester oral glucose tolerance test (OGTT) compared with women who have a normal first trimester HbA1C. Patients and methods The study was conducted at the Obstetrics and Gynecology Department of Sayed Galal University Hospital, Al-Azhar University, during the period between August 2018 and August 2019. The study included 121 pregnant women who regularly attended the outpatient clinic in the first trimester for antenatal care and who were subjected to personal, menstrual, obstetric, past, medical, and family history; general and abdominal examination; ultrasonography and measurement of HbA1C and OGTT. Results The present study showed a statistically significant difference between women with HbA1C value in relation to prepregnancy BMI, pregnancy BMI, gestational age, method of screening, development of GDM, and at 0 h and after 1 h according to fasting value from OGTT result. Conclusion HbA1C level is a good test for identifying patients at high risk of development of GDM. It has a prognostic value in the obese population. Its value has been demonstrated when it is done during the first trimester and up to 20 weeks of gestation. This information may help in GDM screening and treatment.